Mandibular Canine Dimorphism in Establishing Sex Identity in the Lebanese Population - Fouad Ayoub; Loubna Shamseddine; Mohamad Rifai; Antoine Cassia; Randa Diab; Ibrahim Zaarour; Maria Saadeh; Georges Rouhana (International Journal of Dentistry)
Background and Objective. In forensic investigations, mandibular canines provide excellent materials to identify gender since they are more likely to survive disasters. The objective of this study was to investigate gender dimorphism by comparing the mesiodistal width of mandibular permanent canines and intercanine distance in a group of Lebanese population. Methods. Participants consisted of undergraduate students from the School of Dentistry, Lebanese University, for two academic years who fulfilled the inclusion criteria. Canine widths and intercanine distance were measured by one operator directly on dental casts using a digital caliper. Results. One hundred thirty-three Lebanese dental students (54 males and 69 females) aged 18–25 were included in the study. The intercanine distance was significantly greater in males (P value < 0.0001). The right and the left canine widths were significantly greater in males than in females (P value < 0.0001). However, no significant difference was found between left and right canines for males (P value > 0.05) and females (P value > 0.05). The mean width of canine was greater than 7.188 mm for males. Conclusion. The parameters measured in the present study are of great help in sex identification in forensic investigations in the Lebanese adult population.